Trädföryngring i låga gropar uppkomna vid brand i boreal naturskog - Helmersson, Lovisa (2006)
This study was conducted in the "Kåtaberget" forest reserve in Västerbotten in the summer of 1999. In the summer of 1995, a prescribed burning was performed in the reserve. In some places where coarse dry woody debris (logs and stumps) was present, the fire consumed the wood, as well as parts of the humus layer, creating deep-burned patches. The low intensity ground fire also created dead woody debris by burning off living trees with open fire scars, as well as standing dead trees.